Is information enough? The case of Republicans and climate change - Monika Pompeo; Nina Serdarevic (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2021)
One of the most important determinants when it comes to climate change attitudes is political partisanship. While both Democrats and Republicans underestimate the share of their in-groups that believe climate change is happening, this perception gap is wider for Republicans. Using a sample of Republican respondents, we examine their beliefs about climate change and the perceived distribution of climate change attitudes of either other Americans or Republicans. Then, to generate exogenous variation in beliefs, we provide respondents in the treatment groups with the actual distribution of either American or Republican attitudes towards climate change. Our results highlight the importance of distinguishing between beliefs and behaviour when assessing the effect of information on issues that fall strongly along party lines. While information alters the respondents' beliefs about the Republican Party's stance on climate change, it is not enough to instigate a change in individual donation behaviour.
Keywords: J16; C91; D01; 330; Republicans; partisanship; climate change; social norms; information; online experiment